1974
DOI: 10.1111/j.1365-2125.1974.tb00241.x
|View full text |Cite
|
Sign up to set email alerts
|

THE INFLUENCE OF URINARY pH ON THE ELIMINATION OF MEXILETINE

Abstract: 1 The plasma elimination half-life of mexiletine was measured in four subjects when the urine was rendered (a) acidic and (b) alkaline. 2 Urinary acidification (pH 5.0) was associated with a plasma elimination half-life of 2.8 h and 57.5% of the intravenous dose was excreted in the urine within 48 hours. When the urine was alkaline (pH 8.0) the half-life increased to 8.6 h with negligible amounts of drug appearing in the urine. 3 Urinary pH varies widely in cardiac patients and should be controlled or monitore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…The results of this study confirm the observations of Kiddie, Kaye & Turner (1974) that both urinary excretion and plasma concentration of mexiletine are affected by urinary pH. The investigators in that study modified their volunteer's urinary pH to produce the effect, but we have been able to demonstrate it during spontaneous fluctuations in urinary pH.…”
Section: Discussionsupporting
confidence: 88%
“…The results of this study confirm the observations of Kiddie, Kaye & Turner (1974) that both urinary excretion and plasma concentration of mexiletine are affected by urinary pH. The investigators in that study modified their volunteer's urinary pH to produce the effect, but we have been able to demonstrate it during spontaneous fluctuations in urinary pH.…”
Section: Discussionsupporting
confidence: 88%
“…Between individual patients there were great variations in the kinetics with all modes of administration and this was reflected in the great variation in plasma concentrations. Kiddie, Kaye, Turner & Shaw (1974) suggested that this variation might partly be due to fluctuations in urinary pH. They showed that altering the pH of the urine markedly affected the elimination half-life of mexiletine by altering the urinary excretion of unchanged drug.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the metabolic processes involved, it is possible that the rate of metabolism may be influenced by smoking or exposure to enzyme-inducing agents such as phenobarbitone, The percentage of unchanged drug in the urine is pH-dependent. At normal urinary pH, amounts of 10-23 %of ingested doses are recovered unchanged, but this value rises to almost 50% at pH 5.0 and falls to almost negligible amounts at pH 8.0 (9,10).…”
Section: Discussionmentioning
confidence: 95%